INFORMATION ASYMMETRY: EVIDENCE FROM IRAN LISTED COMPANIES - Roudaki, Jamal; Babajani, Jafar; Tahriri, Arash (The International Journal of Accounting and Business Society, 2016)
Inherent in the International and indigenous accounting standards is managerial discretion in the application of accounting methods, preparation of financial reports and disclosures. Extent literature indicates that almost all companies are engaged in some type of earnings management (Healy, 1985; Perry & Williams, 1994; Defond & Jiambalvo, 1994; Jordon, Clark, & Pate, 2008). A crucial question posed for accounting research is to identify the environmental conditions under which managerial discretion (i.e. accounting choices) are exercised. Using empirical analysis this paper investigates one of the fundamental conditions of earnings management, information asymmetry between managers and investors. When information asymmetry is high, stakeholders including investors do not have sufficient resources, incentives, or access to relevant information to monitor managers’ actions, which gives rise to earnings management. Empirical results show that the level of information asymmetry index which is the combination of five important Tehran Stock Exchange (TSE) relevant proxies (volume of trade, stock price variation, P/E ratio, number of trading days and firm age) has a positive statistically significant effect on the extent of earnings management practiced by companies listed on the TSE.